Growth determinants in Ecuadorian companies - Simbaña, Luis Enrique (2017)
Purpose: The current article explores the relationship between a set of variables, with special focus on innovation, and the company growth, which is considered one of the main drivers of the country economies.Methodology: The present research contributes to discussion about factors that motivate company growth, using innovation measure as an explanatory variable, by analysing a sample of 41.333 Ecuadorian companies from all economic sectors for the period of 2000-2013. For the research purpose a static panel data model with fixed effects is used.Findings: Measuring company growth through sales and employment, it is found that size and indebtedness have a negative impact on both growth measures. However, age and innovation show to be significant only on net sales growth. The result of analysis of innovation variable is possible that is related to the proper management of innovation in companies.Research limitations: The scope of the study is limited to the analysis limited liability companies and S.A. (corporations). As a result, consortia, transnational and multinational corporations are not considered in the analysis.Originality/value: The current research could be considered one of the first works that address the growth in Latin America and in particular the first one in Ecuador. Keywords: size, age, debt, innovation, company growth, Ecuador.  [PT]Título: "Determinantes do crescimento em empresas equatorianas"ResumoObjetivos: O presente artigo explora a relação entre um conjunto de variáveis, com foco especial na inovação, e o crescimento da empresa, considerado um dos principais motores das economias do país.Metodologia: A presente pesquisa contribui para a discussão de fatores que motivam o crescimento da empresa, utilizando a medida da inovação como variável explicativa, analisando uma amostra de 41.333 empresas equatorianas de todos os setores da economia no período de 2000-2013. Para fins de pesquisa, é utilizado um modelo de dados de painel estático com efeitos fixos.Resultados: Medindo o crescimento da empresa por meio de vendas e emprego, verifica-se que tamanho e endividamento têm um impacto negativo em ambas as medidas de crescimento. No entanto, idade e inovação mostram-se significativas apenas no crescimento das vendas líquidas. O resultado da análise da variável inovação é possível, relacionado ao gerenciamento adequado da inovação nas empresas.Limitações: o escopo do estudo é limitado às empresas de responsabilidade limitada de análise e à S.A. (empresas). Como resultado, consórcios, corporações transnacionais e multinacionais não são consideradas na análise.Originalidade/valor: A pesquisa atual pode ser considerada um dos primeiros trabalhos que abordam o crescimento na América Latina e, em particular, o primeiro no Equador. Palavras-chave: tamanho, idade, dívida, inovação, crescimento da empresa, Equador.